2011
DOI: 10.1007/s12031-011-9523-5
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase B (Akt) and Mitogen-Activated Protein Kinase p38α in Retinal Ischemic Post-Conditioning

Abstract: In previous studies, it was shown that post-conditioning, a transient period of brief ischemia following prolonged severe ischemia in the retina, could provide significant improvement in post-ischemic recovery, attenuation of cell loss, and decreased apoptosis. However, the mechanisms of post-conditioning in the retina have not been elucidated. We hypothesized that two kinases, mitogen-activated protein kinase p38α and protein kinase B (Akt), were involved in the mechanism of post-conditioning. Ischemia was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Given our previously demonstrated essential role of Akt in retinal Post-C [7], it was not surprising that the PI3K-Akt pathway had a large number of differentially regulated genes in ischemia and Post-C. Many of these, such as the growth factors (e.g., Fgf14), the cytokines (e.g., Il6r, Il6), integrins (e.g., Itga4), receptor tyrosine kinase (e.g., Epha2), are involved in binding to cellular receptors and activation of the PI3K and Akt signaling pathways [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our previously demonstrated essential role of Akt in retinal Post-C [7], it was not surprising that the PI3K-Akt pathway had a large number of differentially regulated genes in ischemia and Post-C. Many of these, such as the growth factors (e.g., Fgf14), the cytokines (e.g., Il6r, Il6), integrins (e.g., Itga4), receptor tyrosine kinase (e.g., Epha2), are involved in binding to cellular receptors and activation of the PI3K and Akt signaling pathways [58].…”
Section: Discussionmentioning
confidence: 99%
“…Post-C attenuated apoptotic cell death [2]. Also, Post-C required activation of Akt, tied to numerous downstream cell survival mediators [7]. It is likely that multiple signaling pathways and altered gene expression are involved in the neuroprotective mechanism of Post-C.…”
Section: Introductionmentioning
confidence: 99%
“…The ERG a-and b-waves were expressed as normalized intensity-response plots with stimulus intensity (log cd s/m 2 ) on the X-axis, and corresponding percent recovery of baseline on the Y-axis, as we previously reported [6,49,50]. Recorded amplitude, time course, and intensity were exported and analyzed in Matlab 2011a (MathWorks, Natick, MA) as previously described [6,[48][49][50]. ERG waveform recovery after ischemia was corrected for day-to-day variation and reference to the non-ischemic eyes as previously described [5,7].…”
Section: Electroretinographymentioning
confidence: 99%
“…Several studies have demonstrated that ischemic conditioning protected retinal function and histology from ischemia–reperfusion injury, when applied before experimental retinal ischemia (preconditioning) and after (postconditioning) reperfusion (Fernandez et al, 2009 b ; Dreixler et al, 2011 a , b ). The preconditioning and postconditioning initiate and potentiate endogenous protective mechanisms, which subsequently diminish reperfusion injury through neutralizing ROS (Zhang et al, 2002; Obolensky et al, 2008).…”
mentioning
confidence: 99%